Modified charcoal and ferromanganese double-metal hydroxide composite material and preparation method thereof
By pyrolyzing straws, and loading ferromanganese bimetallic hydroxide on its surface, forming modified biochar and ferromanganese bimetallic hydroxide composites, the cost and operation of existing wastewater treatment technology is solved. Complex problems have achieved the effect of efficiently removing pollutants.
Patent Information
- Application Number
- CN202411974914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sewage treatment technology has problems such as high cost, complex operation, and easy to produce secondary pollution, making it difficult to effectively improve the adsorption performance and stability of biochar made from straw.
Biochar was prepared by pyrolyzing the straw, and the ferromanganese bimetal hydroxide was loaded on the surface of the biochar by chemical methods to form a modified biochar and ferromanganese bimetal hydroxide composite.
The composite material exhibits efficient adsorption performance and stability in wastewater treatment, which can effectively remove heavy metal ions and organic pollutants in water, reduce treatment costs, and improve treatment efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to a modified biochar and manganese-iron double metal hydroxide composite material and a preparation method thereof. Background Art
[0002] As an abundant agricultural waste, straw has the characteristics of abundant reserves, low cost and renewable. Through pyrolysis and other treatment technologies, straw can be converted into biochar (BC), which has a high specific surface area and rich pore structure, which is conducive to the adsorption and removal of pollutants. Manganese iron double hydroxide (MnFe-LDH), as a layered double hydroxide, has a high specific surface area and excellent catalytic performance, showing broad application prospects in the field of wastewater treatment. By loading it on biochar, the adsorption and catalytic properties of the material can be further improved.
[0003] In the field of sewage treatment, traditional treatment methods such as chemical precipitation, membrane separation, ion exchange, etc. have problems such as high cost, complex operation, and easy secondary pollution. Adsorption method has gradually become a research hotspot in the field of wastewater treatment due to its advantages such as simple operation, low cost, and easy recycling. However, how to use straw and manganese iron metal hydroxide to improve the adsorption performance of biochar made from straw and improve the stability of biochar is a difficult problem that needs to be solved at present. Summary of the invention
[0004] The present invention discloses a method for preparing a composite material of modified biochar and manganese iron double metal hydroxide, wherein biochar is obtained by pyrolysis of straw; and then manganese iron double metal hydroxide is loaded on the surface of biochar by chemical method. This preparation process involves multiple steps such as mixing, stirring, precipitation, washing, and drying to ensure that manganese iron double metal hydroxide can be evenly and firmly attached to the biochar. Due to its unique structure and properties, this composite material shows broad application prospects in the fields of sewage treatment, environmental governance, etc. For example, it can be used as an adsorbent to remove harmful substances such as heavy metal ions and organic pollutants in water, thereby purifying water quality and protecting water resources.
[0005] The present invention adopts the following scheme: A method for preparing a composite material of modified biochar and manganese iron double hydroxide comprises the following steps: (1) Place the agricultural and forestry waste in an ultrasonic cleaner to clean off surface impurities, and then dry it for later use; (2) The dried agricultural and forestry waste materials are put into a crusher for crushing, then sieved, packaged, dried and stored at room temperature for later use; (3) Weighing a certain amount of agricultural and forestry waste material powder into a tubular furnace reactor, pyrolyzing it under a N2 atmosphere to prepare biochar, grinding and sieving it, and then packaging it in a centrifuge tube for later use; (4) Weigh Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in a molar ratio of 3:1, dissolve them in H2O by ultrasonication and set aside; (5) Weigh NaOH and Na2CO3 in a molar ratio of 2:1, dissolve them in H2O by ultrasonication, and prepare a mixed alkali solution for later use; (6) Weigh a certain amount of biochar powder and a certain amount of C2H4O2S, C4H6O3 and H2SO4 and mix them by ultrasonication; wherein the mass-to-liquid ratio of biochar powder to C2H4O2S is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to C4H6O3 is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to H2S04 is 1 (g):0.05 (ml); after cooling to room temperature, place it in a constant temperature forced air drying oven for constant temperature modification to obtain thiol-modified biochar, and then wash, dry, grind and sieve it, then package it for later use; (7) Weighing a certain amount of the thiol-modified biochar and H2O into a mixing container and placing it in a constant temperature water bath for preheating; (8) The prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is evenly and slowly injected into the mixing container, and the mass-to-liquid ratio of the thiol-modified biochar to the Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is controlled at 0.3~1.2 (g): 3~10 (ml), during which analytical pure NaOH and analytical pure Na2CO3 mixed alkali solution are added regularly to adjust the pH, and the mixture is continuously stirred at a constant temperature to generate a precipitate, and the stirring temperature is 60℃-75℃; (9) The mixing container with the precipitate is taken out and allowed to stand for a period of time. After it is cooled to room temperature, it is placed in a drying oven for mineralization reaction. After the reaction is completed, it is washed, freeze-dried, ground, sieved and packaged to obtain a modified biochar and manganese-iron double metal hydroxide composite material.
[0006] Furthermore, in step (1), the ultrasonic frequency is 90 Hz to 100 Hz, and the time is 10 min to 15 min; the temperature of the blast drying oven is 70° C. to 90° C., and the time is 12 h to 20 h.
[0007] Furthermore, in step (3), the pyrolysis temperature is 550°C-650°C, the heating rate is 5°C / min, the heating time is 2h, and the reaction time is 3h~5h.
[0008] Furthermore, in step (6), the temperature of the blast drying oven is 70°C-90°C, and the time is 10h-18h; the cleaning liquid is H2O and C2H6O.
[0009] Furthermore, in step (9), the standing time is 30 min to 45 min; the mineralization temperature is 70°C-90°C, and the time is 12 h to 20 h; the freezing temperature is ~60°C to ~80°C, and the freezing time is 12 h to 20 h, and the sieving mesh number is 100 mesh.
[0010] Furthermore, in step (7), the mass-to-liquid ratio of the thiol-modified biochar and H2O measured by a pipette is 1 (g):5 (ml); and the temperature of the electromagnetic rotary stirrer is set at 60°C-80°C.
[0011] Furthermore, the sieving mesh number in step (2) is 100 meshes.
[0012] Furthermore, in step (8), the mass-to-liquid ratio of the thiol-modified biochar to the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O is 1 (g):10 (ml), and the stirring temperature is 70°C.
[0013] The present invention also provides a modified biochar and manganese-iron double metal hydroxide composite material, which is prepared by any of the above-mentioned methods for preparing the modified biochar and manganese-iron double metal hydroxide composite material.
[0014] Beneficial effects: In the present invention, biochar is obtained by pyrolyzing agricultural and forestry wastes such as straw; and then manganese iron double metal hydroxide is loaded on the surface of biochar by chemical methods. This preparation process involves multiple steps such as mixing, stirring, precipitation, washing, and drying to ensure that manganese iron double metal hydroxide can be evenly and firmly attached to biochar. The prepared modified straw biochar and manganese iron double metal hydroxide composite material, as a new type of adsorption material, combines the adsorption properties of biochar and the catalytic properties of manganese iron double metal hydroxide, and has a high removal efficiency for heavy metal ions and organic pollutants. In addition, the composite material also has good stability and renewability, which is conducive to reducing wastewater treatment costs and improving treatment efficiency. This scheme shows significant advantages in terms of raw material richness, process simplicity, excellent performance, wide range of application, green environmental protection, and significant economic benefits. These advantages make the composite material have broad application prospects and important research value in the field of wastewater treatment. DETAILED DESCRIPTION
[0015] Example 1 A method for preparing a composite material of modified biochar and manganese iron double hydroxide comprises the following steps: (1) Place agricultural and forestry waste (biochar such as straw, leaves, and pine needles) in an ultrasonic cleaner to remove impurities such as sand on the surface, and then place it in a blast drying oven for drying; the ultrasonic frequency is 90 Hz to 100 Hz, the drying time is 10 min to 15 min; the blast drying oven temperature is 70 ° C to 90 ° C, and the drying time is 12 h to 20 h; (2) The dried agricultural and forestry waste is put into a pulverizer for pulverization, then sieved, packaged, dried and stored at room temperature for later use; the sieve mesh number is 80 mesh to 200 mesh; (3) Weigh a certain amount of clean agricultural and forestry waste powder and place it in a tubular furnace reactor, pyrolyze it under a N2 atmosphere to prepare biochar, grind and sieve it, and then package it in a centrifuge tube for later use; wherein the pyrolysis temperature is 550℃-650℃, the heating rate is 5℃ / min, the heating time is 2h, and the reaction time is 3h~5h; (4) Weigh Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in a molar ratio of 3:1, dissolve them in H2O by ultrasonication and set aside; (5) Weigh NaOH and Na2CO3 in a molar ratio of 2:1, dissolve them in H2O by ultrasonication, and prepare a mixed alkali solution for later use; (6) Weigh a certain amount of biochar powder and a certain amount of C2H4O2S, C4H6O3 and H2SO4 and mix them by ultrasonication, wherein the mass-to-liquid ratio of biochar powder to C2H4O2S is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to C4H6O3 is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to H2SO4 is 1 (g):0.05 (ml); after cooling to room temperature, place it in a constant temperature forced air drying oven for constant temperature modification to obtain thiol-modified biochar, which is then washed, dried, ground, sieved, and packaged for use; here, the temperature of the forced air drying oven is 70℃-90℃, and the drying time is 10h~18h; the cleaning solution can be H2O and C2H6O.
[0016] (7) Weigh a certain amount of the above-mentioned thiol-modified biochar and H2O and place them in a mixing container for preheating in a constant temperature water bath; specifically, the mass-to-liquid ratio of the thiol-modified biochar and H2O measured by a pipette is 1 (g):5 (ml); the temperature of the electromagnetic rotary stirrer is set at 60°C-80°C.
[0017] (8) The prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is evenly and slowly injected into the mixing container, and the mass-to-liquid ratio of the thiol-modified biochar to the Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is controlled at 0.3~1.2 (g): 3~10 (ml), during which analytical pure NaOH and analytical pure Na2CO3 mixed alkali solution are added regularly to adjust the pH, and the mixture is continuously stirred at a constant temperature to generate a precipitate, and the stirring temperature is 60℃-75℃; (9) Taking out the mixing container with the precipitate and letting it stand for a period of time, after cooling it to room temperature, putting it into a drying oven for mineralization reaction, after the reaction is completed, washing it, freeze-drying it, grinding it, sieving it and packaging it to obtain a modified biochar and manganese iron double metal hydroxide composite material; specifically, the standing time is 30min~45min; the mineralization temperature is 70℃-90℃, the time is 12h~20h; the freezing temperature is ~60℃ to ~80℃, the freezing time is 12h~20h, and the sieving mesh number is 100 mesh.
[0018] In step (8), the mass-to-liquid ratio of the thiol-modified biochar to the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O is preferably 1 (g):10 (ml), and the stirring temperature is 70°C. In this embodiment, biochar is also called biomass charcoal. The mixing, stirring, precipitation, washing, drying, freezing and other processes mentioned in this embodiment are all existing processes, and the specific process will not be repeated.
[0019] The preparation method adopted in this scheme has the following advantages: 1. The raw materials are abundant and renewable. As an agricultural waste, straw is widely available and renewable, which greatly reduces the preparation cost of composite materials. Mn and Fe elements are abundant in the earth's crust and are easy to obtain, which is conducive to the large-scale production of composite materials.
[0020] 2. The process is simple and environmentally friendly. The preparation process mainly includes pyrolysis of straw, synthesis of manganese-iron double hydroxide and loading process. The process is relatively simple and easy to operate. The entire preparation process does not require the use of a large amount of harmful chemicals, which is beneficial to environmental protection.
[0021] 3. Excellent and stable performance. Straw biochar (BC) has a high specific surface area and rich pore structure, which is conducive to the adsorption of pollutants. Manganese iron double hydroxide has excellent catalytic properties and can accelerate the removal of pollutants. The composite material formed by the combination of the two has excellent and stable performance and is suitable for a variety of wastewater treatment scenarios.
[0022] Example 2 First, soak the wheat straw in H2O for 5 minutes, clean it with an ultrasonic cleaner at 90Hz for 10 minutes, salvage it into a tray, place it in an electric constant temperature air drying oven at 80℃-8h to dry it to constant weight, crush it with a grinder and pass it through a 100-mesh sieve to obtain wheat straw powder. Take a certain amount of the obtained wheat straw powder and place it in a tubular furnace reactor. In a N2 atmosphere, heat it at 5℃·min ~1 Heating rate, 600℃-4h carbonization, produced wheat straw biochar (defined as BC).
[0023] Then, take about 1g of wheat straw biochar (BC), 5mL (analytical grade) C2H4O2S, 5mL (analytical grade) C4H6O3 and a little (analytical grade) H2O and mix them in a three-necked bottle with ultrasound, cover with plastic wrap and wait for cooling to room temperature, transfer it to an electric constant temperature blast drying oven at 80℃ to react for 20h. When the time limit is reached, use H2O and C2H6O to filter and wash until neutral, and the thiol-modified biochar (SH@BC) is obtained.
[0024] Use an analytical electronic balance to accurately weigh (analytical grade) Mn(NO3)2·4H2O and (analytical grade) Fe(NO3)3·9H2O in a 100mL beaker at a molar ratio of 3:1, dissolve by ultrasonication, and adjust the volume to a 100mL volumetric flask. Prepare two 100mL conical flasks, use a 50mL measuring cylinder to accurately measure 50mL of the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in each conical flask, and place it in a water bath at 65℃ / 20rpm-1h for heating and stirring. During this period, prepare a certain concentration of (analytical grade) NaOH and (analytical grade) Na2CO3 mixed alkali solution.
[0025] The above-mentioned thiol-modified biochar was mixed with H2O at a mass-liquid ratio of 1 (g): 5 (ml), and placed in a water bath for stirring and preheating at 65℃-0.1h. SH@BC was added with the prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution at a mass-liquid ratio of 0.3 (g): 3 (ml) and continued to be stirred at 70℃-1h. During this period, the reaction pH was adjusted to 10-12 with a mixed alkali solution of NaOH and Na2CO3. After the stirring was completed, it was sealed with plastic wrap, precipitated and cooled to room temperature, and then transferred to an electromagnetic constant temperature blast drying oven at 80℃ for mineralization reaction for 20h. The reaction material was filtered with a vacuum pump, and the obtained material was placed in a freeze dryer for freeze drying for 20h. The obtained material was ground, sieved and packaged with an agate mortar to obtain a modified biochar and manganese iron double metal hydroxide composite material SH@BC / MnFe~LDH.
[0026] The dynamic and static adsorption experimental indicators of the modified biochar and manganese iron double hydroxide composite material obtained in this case are as follows: the adsorption amount of heavy metal arsenic under static adsorption conditions (temperature 35°C, concentration 300 mg / L, dosage 50 mg, pH about 5, time 2.5h) is 252.76 mg / g, and the removal rate is 84.25%; the adsorption amount of heavy metal arsenic under dynamic conditions (concentration 100 mg / L, flow rate 1 mL / min, column height 5 cm) is 62.89 mg / g.
[0027] Implementation Case 3: First, soak the wheat straw in H2O for 5 min, clean it with an ultrasonic cleaner at 90 Hz for 10 min, salvage it into a tray, place it in an electric constant temperature blast drying oven at 80℃-8h to dry it to constant weight, crush it with a grinder and pass it through a 100-mesh sieve to obtain wheat straw powder. Take a certain amount of the obtained wheat straw powder and place it in a tubular furnace reactor. In a N2 atmosphere, heat it at 5℃·min ~1 Heating rate, 600℃-4h carbonization, to produce wheat straw biochar (BC).
[0028] Take about 1g of wheat straw biochar (BC), 5mL (analytical grade) C2H4O2S, 5mL (analytical grade) C4H6O3 and a little (analytical grade) H2O in a three-necked bottle and mix them by ultrasonication. Cover with plastic wrap and wait until it cools to room temperature. Transfer it to an electric constant temperature blast drying oven at 80℃ to react for 20h. When the time limit is reached, use H2O and C2H6O to filter and wash it to neutrality in turn to obtain the thiol-modified biochar material SH@BC.
[0029] Use an analytical electronic balance to accurately weigh (analytical grade) Mn(NO3)2·4H2O and (analytical grade) Fe(NO3)3·9H2O in a 100mL beaker at a molar ratio of 3:1, dissolve by ultrasonication, and adjust the volume to a 100mL volumetric flask. Prepare two 100mL conical flasks, use a 50mL measuring cylinder to accurately measure 50mL of the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in each conical flask, and place it in a water bath at 65℃ / 20rpm-1h for heating and stirring. During this period, prepare a certain concentration of (analytical grade) NaOH and (analytical grade) Na2CO3 mixed alkali solution.
[0030] The above-mentioned thiol-modified biochar was mixed with H2O at a mass-liquid ratio of 1 (g): 5 (ml), and placed in a water bath for stirring and preheating at 65℃-0.1h. Then SH@BC was added with the prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution at a mass-liquid ratio of 0.6 (g): 6 (ml) and continued to be stirred at 70℃-1h. During this period, the reaction pH was adjusted to 10~12 with a mixed alkali solution of NaOH and Na2CO3. After the stirring was completed, it was sealed with plastic wrap, precipitated and cooled to room temperature, and then transferred to an electromagnetic constant temperature blast drying oven at 80℃ for mineralization reaction for 20h. The reaction material was filtered with a vacuum pump, and the obtained material was placed in a freeze dryer for freeze drying for 20h. The obtained material was ground, sieved and packaged with an agate mortar to obtain a modified biochar and manganese iron double metal hydroxide composite material SH@BC / MnFe~LDH.
[0031] The dynamic and static adsorption experimental indicators of the modified biochar and manganese iron double hydroxide composite material obtained in this case are as follows: the adsorption amount of heavy metal arsenic under static adsorption conditions (temperature 35°C, concentration 300 mg / L, dosage 50 mg, pH about 5, time 2.5h) is 260.21 mg / g, and the removal rate is 86.73%; the adsorption amount of heavy metal arsenic under dynamic conditions (concentration 100 mg / L, flow rate 1 mL / min, column height 5 cm) is 75.06 mg / g.
[0032] Implementation Case 4: First, soak the wheat straw in H2O for 5 min, clean it with an ultrasonic cleaner at 90 Hz for 10 min, salvage it into a tray, place it in an electric constant temperature blast drying oven at 80℃-8h to dry it to constant weight, crush it with a grinder and pass it through a 100-mesh sieve to obtain wheat straw powder. Take a certain amount of wheat straw powder and place it in a tubular furnace reactor. In a N2 atmosphere, heat it at 5℃·min ~1 Heating rate, 600℃-4h carbonization, to produce wheat straw biochar (BC).
[0033] Take about 1g of wheat straw biochar (BC), 5mL (analytical grade) C2H4O2S, 5mL (analytical grade) C4H6O3 and a little (analytical grade) H2O in a three-necked bottle and mix them by ultrasonication. Cover with plastic wrap and wait until it cools to room temperature. Transfer it to an electric constant temperature blast drying oven at 80℃ to react for 20h. When the time limit is reached, use H2O and C2H6O to filter and wash it in turn until it is neutral, and the material SH@BC is obtained.
[0034] Use an analytical electronic balance to accurately weigh (analytical grade) Mn(NO3)2·4H2O and (analytical grade) Fe(NO3)3·9H2O in a 100mL beaker at a molar ratio of 3:1, dissolve by ultrasonication, and adjust the volume to a 100mL volumetric flask. Prepare two 100mL conical flasks, use a 50mL measuring cylinder to accurately measure 50mL of the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in each conical flask, and place it in a water bath at 65℃ / 20rpm-1h for heating and stirring. During this period, prepare a certain concentration of (analytical grade) NaOH and (analytical grade) Na2CO3 mixed alkali solution.
[0035] The above-mentioned thiol-modified biochar was mixed with H2O at a mass-liquid ratio of 1 (g): 5 (ml), and placed in a water bath for stirring and preheating at 65℃-0.1h. SH@BC was added with the prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution at a mass-liquid ratio of 1 (g): 10 (ml) and continued to be stirred at 70℃-1h. During this period, the reaction pH was adjusted to 10~12 with a mixed alkali solution of NaOH and Na2CO3. After the stirring was completed, it was sealed with plastic wrap, precipitated and cooled to room temperature, and then transferred to an electromagnetic constant temperature blast drying oven at 80℃ for mineralization reaction for 20h. The reaction material was filtered with a vacuum pump, and the obtained material was placed in a freeze dryer for freeze drying for 20h. The obtained material was ground, sieved and packaged with an agate mortar to obtain a modified biochar and manganese iron double metal hydroxide composite material SH@BC / MnFe~LDH.
[0036] The dynamic and static adsorption experimental indicators of the modified biochar and manganese iron double hydroxide composite material obtained in this case are as follows: the adsorption amount of heavy metal arsenic under static adsorption conditions (temperature 35°C, concentration 300 mg / L, dosage 50 mg, pH about 5, time 2.5h) is 298.73 mg / g, and the removal rate is 99.57%; the adsorption amount of heavy metal arsenic under dynamic conditions (concentration 100 mg / L, flow rate 1 mL / min, column height 5 cm) is 82.09 mg / g.
[0037] By comparing Examples 2 to 4, it can be found that the adsorption effect of SH@BC and the prepared mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O is better when the mass-to-liquid ratio is 1 (g):10 (ml).
[0038] Implementation Case 5: First, soak the wheat straw in H2O for 5 minutes, clean it with an ultrasonic cleaner at 90Hz for 10 minutes, salvage it into a tray, place it in an electric constant temperature blast drying oven at 80℃-8h to dry it to constant weight, crush it with a grinder and pass it through a 100-mesh sieve to obtain wheat straw powder. Take a certain amount of the obtained wheat straw powder and place it in a tubular furnace reactor. In a N2 atmosphere, heat it at 5℃·min ~1 Heating rate, 600℃-4h carbonization, to produce wheat straw biochar (BC).
[0039] Take about 1g of wheat straw biochar (BC), 5mL (analytical grade) C2H4O2S, 5mL (analytical grade) C4H6O3 and a little (analytical grade) H2O in a three-necked bottle and mix them by ultrasonication. Cover with plastic wrap and wait until it cools to room temperature. Transfer it to an electric constant temperature blast drying oven at 80℃ to react for 20h. When the time limit is reached, use H2O and C2H6O to filter and wash it in turn until it is neutral, and the material SH@BC is obtained.
[0040] Use an analytical electronic balance to accurately weigh (analytical grade) Mn(NO3)2.4H2O and (analytical grade) Fe(NO3)3.9H2O in a 100mL beaker at a molar ratio of 3:1, dissolve by ultrasonication, and adjust the volume to a 100mL volumetric flask. Prepare two 100mL conical flasks, use a 50mL measuring cylinder to accurately measure 50mL of the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in each conical flask, and place it in a water bath at 65℃ / 20rpm-1h for heating and stirring. During this period, prepare a certain concentration of (analytical grade) NaOH and (analytical grade) Na2CO3 mixed alkali solution.
[0041] The above-mentioned thiol-modified biochar was mixed with H2O at a mass-liquid ratio of 1 (g): 5 (ml), and placed in a water bath for stirring and preheating at 65℃-0.1h. Then SH@BC was added with the prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution at a mass-liquid ratio of 1 (g): 10 (ml) and continued to be stirred at a constant temperature of 60℃-1h. During this period, the reaction pH was adjusted to 10~12 with a mixed alkali solution of NaOH and Na2CO3. After the stirring was completed, it was sealed with plastic wrap, precipitated and cooled to room temperature, and then transferred to an electromagnetic constant temperature blast drying oven at 80℃ for mineralization reaction for 20h. The reaction material was filtered with a vacuum pump, and the obtained material was placed in a freeze dryer for freeze drying for 20h. The obtained material was ground, sieved and packaged with an agate mortar to obtain a modified biochar and manganese iron double metal hydroxide composite material SH@BC / MnFe~LDH.
[0042] The dynamic and static adsorption experimental indicators of the modified biochar and manganese iron double hydroxide composite material obtained in this case are as follows: the adsorption amount of heavy metal arsenic under static adsorption conditions (temperature 35°C, concentration 300 mg / L, dosage 50 mg, pH about 5, time 2.5h) is 272.39 mg / g, and the removal rate is 90.79%; the adsorption amount of heavy metal arsenic under dynamic conditions (concentration 100 mg / L, flow rate 1 mL / min, column height 5 cm) is 61.37 mg / g.
[0043] Implementation Case 6: First, soak the wheat straw in H2O for 5 minutes, clean it with an ultrasonic cleaner at 90Hz for 10 minutes, salvage it into a tray, place it in an electric constant temperature blast drying oven at 80℃-8h to dry it to constant weight, crush it with a grinder and pass it through a 100-mesh sieve to obtain wheat straw powder. Take a certain amount of the obtained wheat straw powder and place it in a tubular furnace reactor. In a N2 atmosphere, heat it at 5℃·min ~1 Heating rate, 600℃-4h carbonization, to produce wheat straw biochar (BC).
[0044] Take about 1g of wheat straw biochar (BC), 5mL (analytical grade) C2H4O2S, 5mL (analytical grade) C4H6O3 and a little (analytical grade) H2O in a three-necked bottle and mix them by ultrasonication. Cover with plastic wrap and wait until it cools to room temperature. Transfer it to an electric constant temperature blast drying oven at 80℃ to react for 20h. When the time limit is reached, use H2O and C2H6O to filter and wash it in turn until it is neutral, and the material SH@BC is obtained.
[0045] Use an analytical electronic balance to accurately weigh (analytical grade) Mn(NO3)2·4H2O and (analytical grade) Fe(NO3)3·9H2O in a 100mL beaker at a molar ratio of 3:1, dissolve by ultrasonication, and adjust the volume to a 100mL volumetric flask. Prepare two 100mL conical flasks, use a 50mL measuring cylinder to accurately measure 50mL of the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in each conical flask, and place it in a water bath at 65℃ / 20rpm-1h for heating and stirring. During this period, prepare a certain concentration of (analytical grade) NaOH and (analytical grade) Na2CO3 mixed alkali solution.
[0046] The above-mentioned thiol-modified biochar was mixed with H2O at a mass-liquid ratio of 1 (g): 5 (ml), and placed in a water bath for stirring and preheating at 65℃-0.1h. SH@BC was added with the prepared mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O at a mass-liquid ratio of 1 (g): 10 (ml) and continued to be stirred at a constant temperature of 65℃-1h. During this period, the reaction pH was adjusted to 10-12 with a mixed alkali solution of NaOH and Na2CO3. After the stirring was completed, it was sealed with plastic wrap, precipitated and cooled to room temperature, and then transferred to an electromagnetic constant temperature blast drying oven at 80℃ for mineralization reaction for 20h. The reaction material was filtered with a vacuum pump, and the obtained material was placed in a freeze dryer for freeze drying for 20h. The obtained material was ground, sieved and packaged with an agate mortar to obtain a modified biochar and manganese iron double metal hydroxide composite material SH@BC / MnFe~LDH.
[0047] The dynamic and static adsorption experimental indicators of the modified biochar and manganese iron double hydroxide composite material obtained in this case are as follows: the adsorption capacity of heavy metal arsenic under static adsorption conditions (temperature 35°C, concentration 300 mg / L, dosage 50 mg, pH about 5, time 2.5h) is 276.06 mg / g, and the removal rate is 92.02%; the adsorption capacity of heavy metal arsenic under dynamic conditions (concentration 100 mg / L, flow rate 1 mL / min, column height 5 cm) is 68.95 mg / g.
[0048] From the comparison of the above Examples 2 to 6, it can be seen that after SH@BC is added with the prepared mixed solution of Mn(NO3)2.4H2O and Fe(NO3)3.9H2O at a mass-to-liquid ratio of 1 (g):10 (ml) and then stirred at a constant temperature of 70℃-1h, the prepared composite material exhibits excellent desorption effect and removal efficiency in both static adsorption and dynamic adsorption, meeting the application standards for environmental pollution control.
[0049] Embodiment 7: This embodiment provides a modified biochar and manganese iron double metal hydroxide composite material, which is prepared by the modified biochar and manganese iron double metal hydroxide composite material preparation method. The modified biochar and manganese iron double metal hydroxide composite material prepared by the above method has good adsorption performance, so that the composite material has broad application prospects and important research value in the field of wastewater treatment.
[0050] The modified biochar and manganese iron double hydroxide composite material prepared by this embodiment has the following advantages: 1. Efficient removal of pollutants. The composite material can efficiently remove heavy metal ions, organic pollutants and other harmful substances in wastewater, and has a significant effect in purifying water quality.
[0051] 2. Wide range of applications. Composite materials are suitable for a variety of wastewater treatment scenarios, including wastewater, agricultural wastewater, domestic sewage, etc. For different types of wastewater, the best treatment effect can be achieved by adjusting the ratio of the composite materials and treatment conditions.
[0052] 3. Green, environmentally friendly and sustainable. Composite materials are made of straw and manganese iron elements, which are environmentally friendly materials and have no secondary pollution problems. After use, composite materials can be recycled through regeneration, reducing processing costs and reducing resource waste.
[0053] 4. Significant economic benefits. The preparation cost of the material is relatively low, but the treatment efficiency is high, which can significantly reduce the cost of wastewater treatment. The large-scale production and application of composite materials will help promote the resource utilization and sustainable development of straw, and achieve a win-win situation of economic and social benefits.
[0054] It should be understood that the above are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite material of modified biochar and manganese iron double hydroxide, characterized in that: The steps include: (1) Place the agricultural and forestry waste in an ultrasonic cleaner to clean off surface impurities, and then dry it for later use; (2) The dried agricultural and forestry waste materials are put into a crusher for crushing, then sieved, packaged, dried and stored at room temperature for later use; (3) Weighing a certain amount of agricultural and forestry waste material powder into a tubular furnace reactor, pyrolyzing it under a N2 atmosphere to prepare biochar, grinding and sieving it, and then packaging it in a centrifuge tube for later use; (4) Weigh Mn(NO3)2·4H2O and Fe(NO3)3·9H2O in a molar ratio of 3:1, dissolve them in H2O by ultrasonication and set aside; (5) Weigh NaOH and Na2CO3 in a molar ratio of 2:1, dissolve them in H2O by ultrasonication, and prepare a mixed alkali solution for later use; (6) Weigh a certain amount of biochar powder and a certain amount of C2H4O2S, C4H6O3 and H2SO4 and mix them by ultrasonication, wherein the mass-to-liquid ratio of biochar powder to C2H4O2S is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to C4H6O3 is 1 (g):5 (ml); the mass-to-liquid ratio of biochar powder to H2S04 is 1 (g):0.05 (ml); after cooling to room temperature, place it in a constant temperature forced air drying oven for constant temperature modification to obtain thiol-modified biochar, and then wash, dry, grind and sieve it, then package it for later use; (7) Weigh a certain amount of the above-mentioned thiol-modified biochar and H2O and place them in a mixing container for preheating in a constant temperature water bath; (8) The prepared Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is evenly and slowly injected into the mixing container, and the mass-to-liquid ratio of the thiol-modified biochar to the Mn(NO3)2·4H2O and Fe(NO3)3·9H2O mixed solution is controlled at 0.3~1.2 (g): 3~10 (ml), during which analytical pure NaOH and analytical pure Na2CO3 mixed alkali solution are added regularly to adjust the pH, and the mixture is continuously stirred at a constant temperature to generate a precipitate, and the stirring temperature is 60℃-75℃; (9) The mixing container with the precipitate is taken out and allowed to stand for a period of time. After it is cooled to room temperature, it is placed in a drying oven for mineralization reaction. After the reaction is completed, it is washed, freeze-dried, ground, sieved and packaged to obtain a modified biochar and manganese-iron double metal hydroxide composite material.
2. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: In step (1), the ultrasonic frequency is 90 Hz to 100 Hz, and the time is 10 min to 15 min; the temperature of the blast drying oven is 70° C. to 90° C., and the time is 12 h to 20 h.
3. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: In step (3), the pyrolysis temperature is 550°C-650°C, the heating rate is 5°C / min, the heating time is 2h, and the reaction time is 3h~5h.
4. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: In step (6), the temperature of the blast drying oven is 70°C-90°C, and the time is 10h-18h; the cleaning liquid is H2O and C2H6O.
5. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: In step (9), the standing time is 30 min to 45 min; the mineralization temperature is 70°C-90°C, and the time is 12 h to 20 h; the freezing temperature is ~60°C to ~80°C, and the freezing time is 12 h to 20 h, and the sieving mesh number is 100 mesh.
6. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: Step (7) Weigh the thiol-modified biochar and H2O measured by a pipette at a mass-to-liquid ratio of 1 (g):5 (ml); set the temperature of the electromagnetic rotary stirrer to 60°C-80°C.
7. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: The sieve mesh number in step (8) is 100 mesh.
8. The method for preparing the composite material of modified biochar and manganese iron double hydroxide according to claim 1, characterized in that: In step (8), the mass-to-liquid ratio of the thiol-modified biochar to the mixed solution of Mn(NO3)2·4H2O and Fe(NO3)3·9H2O is 1 (g):10 (ml), and the stirring temperature is 70°C.
9. A modified biochar and manganese iron double metal hydroxide composite material, characterized in that: The composite material is prepared by the method for preparing the modified biochar and manganese-iron double hydroxide composite material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Passivation agent for Cd contaminated soil and preparation method thereof
CN108085012A
Sulfydryl modified charcoal based on agricultural wastes, preparation method and application thereof
CN108176361A
Preparation method and application of biochar-Ni / Fe layered double hydroxide composite material
CN109092250A
Preparation method and application of sulfhydrylation biochar for repairing heavy metal polluted water and soil
CN110369486A
Preparation method application of EDTA-intercalated iron-manganese layered bimetal hydroxide
CN110433765A
Cited By
Method for treating thallium-containing wastewater by using biochar doped with metal oxide
CN121292571A
Supported biomineralized composite material as well as preparation method and application thereof
CN122399753A